Disrespect and abuse experienced by women giving birth in public health facilities of Eastern Ethiopia: a multicenter cross-sectional study - Sintayehu Gebregziabher; Behailu Hawulte; Legesse Abera; Abel Tibebu Goshu (Journal of International Medical Research, 2022)
Objective We assessed the magnitude of disrespect and abuse experienced by women giving birth at public health facilities in Dire Dawa, Eastern Ethiopia. Methods We conducted a facility-based quantitative cross-sectional study in Dire Dawa City Administration from 21 October to 8 December 2020. We used a pre-tested structured questionnaire to interview 555 randomly selected women who gave birth in public health facilities during the study period. Bivariate and multivariate logistic regression analysis was performed in statistical analysis. Results Among 555 women, 473 (85.2%) reported having experienced at least one form of disrespect and abuse. Giving birth at a hospital (adjusted odds ratio [AOR] = 4.15; 95% confidence interval [CI], 2.29–7.51) and being attended by male providers (AOR = 3.27; 95% CI, 1.57–6.81), as well as being attended by three or four providers (AOR = 0.44; 95% CI, 0.22–0.88) and delivering at night (AOR = 0.27; 95% CI, 0.15–0.48) were significantly associated with greater or less likelihood, respectively, of disrespect and abuse. Conclusion We revealed an unacceptable level of disrespect and abuse toward women giving birth at public health facilities. Health care providers must understand the importance of respectful maternity care. The city's health bureau should conduct provider training and enforce adherence to respectful care.